2006
DOI: 10.14411/eje.2006.036
|View full text |Cite
|
Sign up to set email alerts
|

A karyotype study on the pseudoscorpion families Geogarypidae, Garypinidae and Olpiidae (Arachnida: Pseudoscorpiones)

Abstract: Abstract. The karyotypes of pseudoscorpions of three families, Geogarypidae, Garypinidae and Olpiidae (Arachnida: Pseudoscorpiones), were studied for the first time. Three species of the genus Geogarypus from the family Geogarypidae and 10 species belonging to 8 genera from the family Olpiidae were studied. In the genus Geogarypus the diploid chromosome numbers of males range from 15 to 23. In the family Olpiidae the male chromosome numbers vary greatly, from 7 to 23. The male karyotype of single studied membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…However, the morphology of the X chromosome is usually metacentric in this order (Šťáhlavský et al 2012a, 2013, Kotrbová et al 2016), whereas an acrocentric X was identified in N.slovacum . This morphology of the X chromosome was previously documented in only one population of Olpiumpallipes (Lucas, 1846) (Olpiidae) within pseudoscorpions (Šťáhlavský et al 2006). It was supposed to be an effect of pericentric inversion from Greece in the population concerned.…”
Section: Discussionsupporting
confidence: 66%
“…However, the morphology of the X chromosome is usually metacentric in this order (Šťáhlavský et al 2012a, 2013, Kotrbová et al 2016), whereas an acrocentric X was identified in N.slovacum . This morphology of the X chromosome was previously documented in only one population of Olpiumpallipes (Lucas, 1846) (Olpiidae) within pseudoscorpions (Šťáhlavský et al 2006). It was supposed to be an effect of pericentric inversion from Greece in the population concerned.…”
Section: Discussionsupporting
confidence: 66%
“…The wide diversity of chromosome numbers found in Opiliones also occurs in two related orders, Pseudoscorpiones and Scorpiones (Shanahan 1989;Sˇa´hlavsky´et al 2006). These orders, together with Solifugae, form the clade (Pseudoscorpiones + Solifugae) Scorpiones, that constitutes the sistergroup of Opiliones (Shultz 1990;Wheeler and Hayashi 1998;Giribet et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As stated above, amblypygids exhibit a considerable karyotype differentiation. Besides amblypygids, a high diversity of karyotypes has also been found in other arachnid orders, namely in spiders (2n = 5-152; [48][49][50]), scorpions (2n = 5-186; [51,52]), harvestmen (2n = 10-109; [53,54]), and pseudoscorpions (2n = 7-143; [55,56]). Compared to other arachnids, the amblypygid radiation, which took place before the collapse of Pangea and Gondwana, led to the occurrence of amblypygids in almost all continents [22]-a condition also notable in charinids [19][20][21].…”
Section: Patterns Of Karyotype Differentiationmentioning
confidence: 96%